(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
– One of the most common forms of decomposition caused by concrete structures is surface wear. This carrier may serve as a catalyst for other forms of damage, such as, for example, steel cracks and corrosion. The purpose of the project is to discuss the most important aspects of concrete wear and tear. Common resources and grinding mechanisms have been identified. It takes into account the effects of the components, composition and strength of the composites and the practical construction of concrete wear resistance. This project identifies the usual test methods that determine the wear resistance of the concrete. Finally, this project highlights several key points for future work with concrete abrasion resistance.